(untitled) (Research, Society and Development, 2020)
In view of the growing concern with quality, it is essential that the food industries adopt effective measures to ensure the safety and integrity of food, among them the HACCP. The objective was to offer subsidies to industries that manufacture / produce whey protein and to professionals who work in the prevention and control of quality and safety of foods. For the preparation of the HACCP plan for whey protein, Ordinance no 46 of 10 February 1994 was recommended, which follows the Codex Alimentaris Commission model, presenting seven basic principles. The results show that whey protein is a product in which it deserves special attention because it presents several possible agents of contamination in its production process. Thus, HACCP has proven to be an excellent tool to guarantee quality in all stages of whey protein production, as it becomes possible to analyze and identify all biological, physical and chemical agents, in which they can compromise quality of the final product. This becomes even more important, since it is on the rise, both in sports and in its incorporation in various preparations by the food industries, due to its functional properties.